A note of optical error diagnosis of parabolic trough concentrator based on flux image. (February 2020) - Song, Jifeng; Wang, Wenmo; Niu, Yisen; Wang, Juntao; Yu, Hai
Highlights: Direct photograph of concentrated flux of parabolic trough concentrator. Flux image-based diagnosis of solar tracking error and slope error. Diagnosis based on flux shape without intensity calibration. Abstract: In practical applications, there are many optical errors in the parabolic trough concentrators (PTC), such as mirror slope errors and tracking errors. Image detection is a no contact technique that has a potential to diagnose the optical errors at large plants in use. In this study, a CCD (Charge Coupled Device) camera was used to directly observe the absorber, and the images of the flux peaks were successful obtained. The CCD image showed two bright peaks on the outer wall of the tubular absorber. By comparing the CCD image with the simulation results, the concave deformation of the parabolic mirror was diagnosed, and the slope error of the parabolic mirror was figured out. The images also revealed that sun tracking errors can cause a synchronous shift in the flux. The flux image method does not influence the normal operation of PTC and is an on-line method, which facilitates the field application.